Enabling Human Development through Poshan Abhiyaan: A Situation Analysis - Mobar Roy, Sonal (International Journal of Psychosocial Rehabilitation, 2024)
Ensuring healthy lives and promoting the well-being at all ages is essential to achieve sustainable development asentailed in SDG 3. With this as the roadmap, the government of India has launched the Poshan Abhiyaan (NationalNutrition Mission) to improve nutritional outcomes for children, pregnant women, lactating mothers and adolescentgirls. Conceptualized as a Jan Andolan or ‘people’s actions’ for promoting inclusive participation, it aims atreaching every household with the message of nutrition. The author examines the implementation of the program asan agency and the enhancement of human development thus envisioned through Sen’s Capability Approach